Causal Effect of Economic Indicators on Indian Automobile Sector - Yelamanchili, Rama Krishna (International Journal of Economics and Financial Issues, 2020)
In this paper we examine the co-movement and casual relationship between economic indicators and automobile index. We postulate that leading and coincident economic indicators will help explain, cause, and predict movements in automobile index. To test our hypotheses we source data for four coincident indicators, namely Index of Industrial Production (IIP); Index of Manufacture of Motor Vehicles, Trailers and Semi-trailers (MVI); Index of Manufacture of Other Transport Equipment (TEI); and West Texas Intermediate (WTI) crude oil price, for leading indicator we use Bombay Stock Exchange (BSE) sensitive index (SENSEX). We consider BSE's AUTO index as proxy for Indian Automobile Industry. We collect monthly data of our study variables from April 2012 to June 2019. We break our full sample into two sub-samples based on break point in AUTO index and run separate analysis for each sample period. We find significant contemporaneous co-movements between SENSEX and AUTO index. In contrast to our hypothesis AUTO index cause SENSEX in all the three sample periods. Granger test confirms this result with different lags. In addition, we also find evidence for causation from AUTO index to MVI and TEI with five and three lags respectively in our second sub-sample period. Our results indicate that automobile industry influence Indian stock markets and automobile industrial production. Our results suggest that policy makers and regulators should be vigilant in making policies pertaining to automobile industry and should consider the repercussions of their decisions, because wrong policy decisions about auto industry may hurt the Indian economy. Keywords: Indian economy, Indian stock markets, automobile industry performance, policy implications, regulatory norms JEL Classifications: G11, G18, E23, E32 DOI: https://doi.org/10.32479/ijefi.9175